Utilization of non-timber forest products in the context of forest management in the face of climate change - Parera, Lydia Riekie; Putuhena, Jusmy D. (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This article explores the utilization of non-timber forest products (NTFPs) within the framework of forest management, particularly in the context of climate change. Employing a qualitative methodology through a comprehensive literature review, the study examines the significance of NTFPs in enhancing forest resilience and supporting local communities. The findings indicate that NTFPs play a crucial role in sustainable forest management by providing alternative livelihoods, contributing to biodiversity conservation, and mitigating the impacts of climate change. The research highlights the importance of integrating NTFPs into forest management strategies, emphasizing their potential to foster adaptive practices that enhance ecosystem services. Furthermore, the study identifies challenges such as overharvesting, lack of market access, and insufficient policy support that hinder the sustainable utilization of NTFPs. Recommendations are provided for policymakers and forest managers to promote the sustainable management of NTFPs, including the development of community-based management approaches and the establishment of fair trade practices. This article contributes to the understanding of the multifaceted role of NTFPs in forest ecosystems and underscores the need for innovative strategies that align conservation goals with the socio-economic needs of local communities in the face of climate change.